Enhancing English Language Learning In Tertiary Education Through Blended Approaches: A Bangladesh Perspective - Md. Fajlay Rabbi; Md. Sefatul Islam; Md. Jamil Hossain (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: Main purpose of this study to investigates the implications of adopting blended approaches in enhancing English language proficiency, bridging the digital divide, and preparing students for the demands of a globalized world. Through a Bangladesh perspective, this research seeks to illuminate the transformative power of blended learning. Methodology: This research employs a qualitative approach. In depth Interviews (IDI) and FGDs has been administered to thirty facilitators and thirty students to measure benefits and challenges associated with blended learning. Additionally, Interviews with ten pedagogy experts has provide insights into successful implementation strategies. Data has been analyzed thematically. Main Findings: Research findings show that by blending technology with traditional pedagogy, this approach prepares students for a world where adaptability and digital literacy are paramount. The success of this approach relies on the collaborative efforts of educational institutions, instructors, and students, all working towards a holistic and dynamic learning experience that empowers students to thrive in an interconnected global society. Novelty/Originality of this study: This study adds additional knowledge of the challenges and efforts associated with blended approaches to English language learning in tertiary education in Bangladesh.The study's findings can be used as a guide for interested parties, including educators and institutions of higher learning, to address the issues with English language teaching and learning in tertiary education and improve student language learning quality.